2005
DOI: 10.1039/b502917a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and electrochemical studies of mixed ligand complexes of ruthenium(ii) with DNA

Abstract: Two mixed ligand complexes of ruthenium(ii) [Ru(bzimpy)(bpy)(OH(2))](2+) (1) and [Ru(bzimpy)(phen)(OH(2))](2+) (2) have been synthesized and characterized by FAB mass, (1)H NMR, cyclic voltammetry and spectroelectrochemical measurements. Controlled potential electrolysis of these complexes results in the conversion of ruthenium(ii) to ruthenium(iii) at 0.6 V and ruthenium(iii) to ruthenium(iv) at 0.8 V vs. SCE. The binding constant of these complexes with DNA has been determined electrochemically and found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(42 citation statements)
references
References 27 publications
1
40
0
1
Order By: Relevance
“…These results indicated that the complex may possess the potent DNA cleavage ability at the concentrations higher than 80 µM. 38) In summary, the results of fluorescence emission titration indicated that the complex had a low quenching constant K q …”
Section: )mentioning
confidence: 80%
“…These results indicated that the complex may possess the potent DNA cleavage ability at the concentrations higher than 80 µM. 38) In summary, the results of fluorescence emission titration indicated that the complex had a low quenching constant K q …”
Section: )mentioning
confidence: 80%
“…[11] Ruthenium(II) polypyridyl complexes have attracted comprehensive attention due to their significance in the development of new therapeutic agents and novel nucleic acid structural probes. [12][13][14] A number of dinuclear iron complexes are known to exhibit hydrolytic cleavage of duplex DNA. [15][16] Nickel(II) and cobalt(II) macrocyclic complexes have been [a] Chemical Laboratory, Central Leather Research Institute, Adyar, Chennai, 600020 Tamil Nadu, India Fax: +91-44-2491-1589 E-mail: bunair@clri.info is more uniformly distributed in the case of tolylterpyridine (complex 1), which possibly leads to better stacking interactions with the DNA bases and hence a higher binding constant value for complex 1.…”
Section: Introductionmentioning
confidence: 99%
“…The formal potential Ef shift slightly towards the positive side and is attributed to characteristic behaviour of intercalation of the complexes into the DNA double-helix and suggests that extract bind to DNA at different rates 18 .…”
Section: Electrochemical Methodsmentioning
confidence: 96%